Characteristic volatiles fingerprints and profiles determination in different grades of coconut oil by HS‐GC‐IMS and HS‐SPME‐GC‐MS. (13th August 2020) - Chang, Ming; Zhao, Pinzhen; Zhang, Tao; Wang, Yong; Guo, Xin; Liu, Ruijie; Jin, Qingzhe; Wang, Xingguo
Summary: Coconut oil has been extensively used in the food industry, but determination of the quality of coconut oil remains challenging. In this study, volatile components of the coconut oils (refined, desiccated or virgin) subjected to different processing methods were identified and compared. Twenty‐six volatile components exhibiting characteristic differences among the three types of coconut oil were screened using headspace solid‐phase microextraction–gas chromatography–mass spectrometry (HS‐SPME‐GC‐MS). Furthermore, ethanol, 1‐propanol and dimethyl ketone could only be determined by using headspace‐gas chromatography–ion mobility spectrometry (HS‐GC‐IMS). The principal component analysis diagrams attained by the volatile component data demonstrated that the coconut oil samples could be clearly classified into three categories. The multivariate analysis results revealed 2‐heptanone and hexanal to be the most promising markers in terms of grade discrimination in coconut oil. The findings are conducive to the development of a new method for the identification of oils with different refining degrees. Abstract : Characterisation and classification of volatiles from coconut oil by HS‐SPME‐GC‐MS and HS‐SPME‐GC‐IMS coupled with an appropriate multivariate analysis have the potential to be used as a non‐destructive way to evaluate coconut oil quality and any other characteristics.